Issuance of Environmental Approvals Based on the Precautionary Principle: A Legal Study - Nuril Firdausiah; Iwan Rachmad Soetijono; Galuh Puspaningrum (Rechtenstudent, 2025)
On October 5 2020 the government and the people's representative council passed a new law, namely Law Number 11 of 2020 concerning Job Creation which raises pros and cons. These changes are based on simplifying licensing. Which changes the nomenclature of environmental permits to environmental approval. Permits are clearly a state administration decision as regulated in Law Number 30 of 2014 concerning Government Administration, whereas normative approval does not have an explicit meaning as a state administration decision. Furthermore, the change in norms is also accompanied by the elimination of the community's right to responsibility towards the government as the permit giver which was originally stipulated in Article 38 of Law Number 32 of 2009 concerning environmental protection and management. Environmental permit violations that occur do not have any impact on the business permit. The government only provides punishment in the form of a warning to violators.